Diferenças dos níveis de pobreza dos países africanos de língua oficial portuguesa (palop) - Spencer, Erica Simone Fernandes (2022)
The general objective of this research is to study the different patterns of development and poverty in Portuguese- Speaking African countries. The data used were collected from specialized sources such as the World Bank, United Nations Organization ( ONU) and United Nations Human Development Report ( HDR) between the years 1998- 2018. The Variables used in the research were GDP per capita, average years of schooling, Literacy rate, rate of access to basic sanitation, rate of access to drinking Water service and finally average life expectancy. The approach of methodology chosen was multi-method that encompasses a qualitative and technical analysis. The quantitative analysis encompasses the calculation of the averages and the coefficients of variation (CV) of several years for each of the chosen indications in order to comparatively verify the performance and development of each country, as well as the determined levels of poverty. From the results we can see how much each of these countries loses by not giving due importance to indicators such as basic sanitation.Either with health and education harmed with thousands of sick people due to sanitary diseases, or with the poor performance of the economy that is not exploited to its potential.Also through this research, it was seen that the cases of Mozambique and Guinea Bissau configure the wort positions of the PALOP, with the worst averages and greater heterogeneity of the analyzed indicators, while in the cases of Cape Verde and São Tomé and Príncipe they correspond to the best positions with the best averages and the greatest homogeneity of the development and socioeconomic indicators studied.